Smart nanomaterials for bioencapsulation - Castro, Guillermo R.; Nadda, Ashok Kumar; Nguyen, Tuan Anh; Sharma, Swati; Gupta, Ram K. (Micro & nano technologies., 2023)
Smart Nanomaterials for Bioencapsulation focuses on the fundamentals, synthesis methods and matrix design for the encapsulation of drugs, drug release, food and nutraceuticals, mechanisms of nano- encapsulated drugs on liposomes, micelles, silica composites, carbon nanotubes, dendrimers, and protein inorganic nanohybrids. Providing detailed information on the encapsulation of food and drug derivatives, the book helps create new and modern approaches for both pharmaceutical and nutritional science. The target delivery of pharmacological agents, as well as food additives under various conditions is covered, including sections on systemic release of drug molecules, minimum loss at non-target sites, the accumulation of diseased tissue or organs, and more. Smart nanomaterial-based nanocarriers protect the loaded molecules from premature degradation in the biological environment and enhance bioavailability for cellular uptake. The tuned properties of smart nanomaterials, such as porosity, pore-volume, surface area-to-volume ratio, coating with inert and labile materials, and more help determine the in vivo performance of the bioencapsulated food and drug derivatives.